Sensory quality of cheddar cheese made with bulk starter and direct to vat starter culture - Musetti, James, author; Stone, Martha, advisor; Bunning, Marisa, committee member; Nair, Mahesh Narayanan, committee member; Miller, Jeff, committee member; Romero, Dennis, committee member (Colorado State University. Libraries, 2024)
The production of cheese in the world consumes around 35% of the total milk production and has increased on average by 4% per year over the past 30 years (Fox et al., 2017). Cheddar consumption had modestly and steadily increased in the past several years in the United States and has increased 2.22% from 9.87 pounds per capita to 10.09 pounds per capita (USDA ERS Dairy Data, n.d.). Over the past several decades modernization of cheddar production in the United States has enabled producers to increase throughput with fewer resources resulting in more efficient production and consistent quality. This includes the common practice of standardizing cheese making procedures on a strict timing basis and using reliable and consistent rate and extent of acidification through culture selection and dosage. One such advancement was the development of defined starter cultures produced in a frozen or lyophilized state to be applied directly to the vat as a direct to vat inoculant (DVI) by the cheesemaker. Previously lactic acid bacterial cultures, defined or natural, were propagated by the cheesemaker prior to cheese production by a preceding fermentation of milk or whey and used to inoculate the milk for cheddar production. The current research investigated if any differences in cheddar cheese biochemical and sensory characteristics exist among cheeses made with bulk starter and DVI technologies. Cheeses were produced using bulk starter culture technology, DVI technology, and DVI technology with pre-acidification then ripened for 90 days. The rate and extent of acidification in the process was analyzed with cheese composition, extent of the catabolism of protein and fat during ripening, and sensory characteristics of the cheese analyzed. MANOVA model analysis reported that the treatments had a significant effect on the cheesemaking process (p=0.00381). Coagulation time was the only response found to be statistically significant (p=0.00081) from the process, biochemical, and sensory responses after mixed model analysis was completed. The make data or milk batch was found to have a significant effect on the cheese production process (p=0.00036), biochemistry (p=0.04391), and sensory characteristics (p=0.00002) of the cheeses. Therefore, it can be concluded that there was no difference in cheddar proteolysis, lipolysis, and sensory characteristics in cheeses manufactured with bulk starter and DVI, and there was no difference in cheddar proteolysis, lipolysis, and sensory characteristics in cheeses manufactured with bulk starter and DVI culture preparations with recipe adjustment for coagulation. The null hypotheses cannot be rejected.
Keywords: cheddar quality; dairy; starter culture; cheese; bulk starter; direct vat starter